Cyclooxygenase (COX)-2 as a potent molecular target for prevention and therapy of oral cancer - Masahiro Urade (Elsevier, 2008)
Cyclooxygenase (COX)-2 is one of two isoforms of COX that is the rate-limiting enzyme in the production of prostaglandin from arachidonic acid. It is induced by stimuli such as mitogens, cytokines, growth factors and tumor promoters, and has been elucidated to be up-regulated not only at the sites of inflammation but also in various cancer tissues such as colon, stomach, breast, lung and head and neck including oral cavity. Overexpression of COX-2 is known to inhibit apoptosis and immune surveillance, promote angiogenesis, increase cancer invasiveness and metastasis. Therefore, COX-2 is considered to be strongly involved in carcinogenesis and tumor growth. In fact, immunohistochemical and Western blot analyses in oral precancerous and cancerous lesions demonstrated that COX-2 expression is increased from epithelial dysplasia to squamous cell carcinoma through carcinoma in situ, with the elevation of cell proliferating activity. The patients with overexpression of COX-2 showed poor prognosis and their overall 5-year survival rate was decreased. Inhibition of COX-2 activity with selective COX-2 inhibitors or antisense RNA resulted in suppression of tumor cell growth and invasion in vitro and prevention of oral carcinogenesis by chemical carcinogens in animal models. In addition, combined use of selective COX-2 inhibitors was found to enhance synergistically the cytocidal effects of anti-cancer drugs and irradiation. From these evidences, it is indicated that COX-2 becomes a potent molecular target for prevention and therapy of oral cancer.